The Quality of Japanese Quail Eggs After Administration of Bifidobacterium sp. and Guazuma ulmifolia Leaf Extract - Lovela, Aprinda Ratna; Lokapirnasari, Widya Paramita; Al-Arif, Mohammad Anam; Soeharsono, Soeharsono; Hidanah, Sri; Warsito, Sunaryo Hadi; Prasinta, Redilla; Hapsari, Tiara; Andriani, Asafarid (Universitas Airlangga, 2023)
This study aimed to determine the effect of Bifidobacterium sp. and Guazuma ulmifolia leaf extract on Japanese quail egg production, including egg mass, haugh unit (HU), and egg yolk colour. A total of 96 quails were in the early stages of production, which were randomized into four treatments and six replications. The treatments were (T0) without Bifidobacterium sp. and G. ulmifolia leaf extract, (T1) 0.2% Bifidobacterium sp., (T2) 0.2% G. ulmifolia leaf extract, and (T3) 0.2% Bifidobacterium sp. + 0.2% G. ulmifolia leaf extract. Egg mass data was collected in the third and fourth week of the treatment period, while the HU data and egg yolk colour were carried out on the last week of the treatment period. The treatment groups showed significant differences in egg mass. Groups T2 and T3 showed significant differences in egg yolk colour. The combination of feed additives can increase the value of HU but not significantly (p>0.05). In conclusion, the combination of 0.2% Bifidobacterium sp. and 0.2% G. ulmifolia leaf extract in drinking water can produce the highest egg quality.